O artesanato e o patrimônio cultural: a produção acadêmica dos programas de pós-graduação em patrimônio cultural - Silveira, Cátia Luciane Silva (2019)
The Brazilian Cultural Heritage concerns more than protected buildings and material assets. The traditions of popular life, the collective ways of doing, the celebrations, the rhythms, and the dances are considered intangible assets of the country, foreseen by the Federal Constitution of 1988 and also by the United Nations Educational, Scientific and Cultural Organization (UNESCO). This research was developed based on the state-of-the-art/knowledge methodology and aimed to conduct a survey and analyze the constitution of the stricto sensu Graduate Programs in Cultural Heritage, from the Sucupira Platform information fields, as well as to list their academic production, concerning handicrafts in the approach of cultural heritage, from 2003 to 2017. From these results, we developed the catalog with the Postgraduate Programs in Cultural Heritage in Brazil, its areas of framing and faculty by area of knowledge in addition to the academic productions that compound the state of knowledge of this research, in order to systematize and disseminate what has been produced about the subject in the academic field. The searches for Post-graduation Programs in the Sucupira Platform, a tool to collect information, perform analysis, and evaluations, serving as a reference base of the National Graduate System - SNPG, allowed listing eight Programs that have the denomination Cultural Heritage, object of the research, totaling ten Masters, Professional Masters and Doctorate courses. The search in the repositories of Universities and Graduate Programs listed by the Sucupira Platform generated ten dissertations and not a single thesis, obeying the search criteria by keyword, title and / or subject.